A same day 'test and treat' model for chronic HCV and HBV infection: Results from two community‐based pilot studies in Egypt. Issue 6 (10th March 2020) - Shiha, Gamal; Soliman, Reham; Serwah, Abdalhamed; Mikhail, Nabiel N. H.; Asselah, Tarik; Easterbrook, Philippa
Abstract: Prompt access to confirmatory viral load testing and staging of liver disease are key barriers in uptake of treatment for chronic hepatitis B and C infection. Our objective was to establish the feasibility of a same day 'test and treat' model in two distinct community‐based settings in Egypt through use of key point‐of‐care (POC) portable tools for HCV and HBV viral load assessment and staging of liver disease followed by treatment initiation. Community sites were a village in northern Egypt (site 1) and a government office in Cairo (site 2). The following model was adopted: community awareness raising in the week before project initiation; site assessment to ensure optimal placement and calibration of equipment and clinical care set‐up; transfer of key portable laboratory instruments to the sites (four cartridge GeneXpert, FibroScan and abdominal ultrasound); screening using rapid diagnostic tests for HCV‐Ab and HBsAg, with immediate venous or finger‐stick blood sampling for HCV‐RNA and HBV‐DNA assay, FibroScan staging of liver disease and ultrasound screening for liver cancer. At site 1, 475 individuals were screened over a single day, 125 were positive for HCV‐Ab and 4 for HBsAg, 43 of 56 new HCV diagnoses were HCV RNA positive, and 3 of 4 HBsAg positive were HBV DNA positive, 40 initiated HCV treatment, and one HBV treatment . At site 2, 3188 individuals were screened over 3 days, 157 were positive for HCV‐Ab, and 27 for HBsAg; 38 of 76 new HCV diagnoses were HCV RNA positive, and 15 of 18 HBsAg positive were HBV‐DNA positive. Across both sites, 78 patients were counselled and initiated on treatment for HCV and 12 for HBV within 3 and 4 hours, respectively, of initial positive rapid diagnostic test result. We have shown the feasibility of a same day 'test and treat' model for chronic HCV and HBV infection in two community‐based settings in Egypt that achieved high levels of linkage to care and initial treatment.